SARS-CoV-2: The Prominent Role of Non-structural Proteins (NSPS) in COVID-19 - Gorla, Uma Sankar; Rao, GSN Koteswara (Indian Journal of Pharmaceutical Education and Research, 2020)
COVID-19, an infectious contagious viral (SARS-CoV-2) disease, associated with morbidity and mortality from respiratory pandemic worldwide. Currently, COVID-19 has no targeted treatment strategies and has been declared by WHO as a global health emergency. SARS-CoV-2, an enveloped, positive-sense, betacoronavirus (βCoV) spreading rapidly due to its potential pre- and asymptomatic transmission (silent transmission). The viral replicase single-stranded genome encodes for two open reading frame genes (orf1a and orf1b), that are translated into two polyproteins, pp1a and pp1b. Viral proteases including papain-like protease (PL-PRO) and chymotrypsin-like protease (3CL-PRO) pre-processes and fragments the polyproteins into 16 non-structural proteins (Nsps) that are assembled into replicase-transcriptase complex and exhibit multiple enzymatic activity. To rationalize their evolutionary success and develop improved control strategies, understanding the main functions and interactions of non-structural proteins of SARS-CoV-2 will be essential. Based on the existing published literature, this review summarizes the knowledge on multiple pathologic functions of Nsps in COVID-19. This review is hoped to help the researchers to understand the significant role of nonstructural proteins in COVID-19 and provide a reference for future studies.
Keywords: COVID-19; SARS-CoV-2; Non-structural proteins; Open reading frames; Polyproteins; Phylogenetic analysis